Pleiotropic effects of statins. Are there opportunities to explain of the phenomenon? - I. A. Latfullin; L. F. Galiullina; I. Z. Rakhmatullin; V. V. Klochkov; A. V. Aganov (Рациональная фармакотерапия в кардиологии, 2015)
A hypothesis that possible pleiotropic features of different statins could be explained by distinctions in their interaction with cell membrane is suggested. Molecular complexes of pravastatin and simvastatin with model of cell membrane were studied by method of nuclear magnetic resonance spectroscopy. It was shown that pravastatin interacts almost exclusively with a surface of cell membrane and, therefore active transport system is needed to deliver pravastatin into the cell. In contrast, simvastatin is located in the inner part of model cell membrane. That’s why it can passively penetrate into organism cells. Perhaps, these differences lead to distinctions of pleiotropic properties of these statins.